Pengaruh Brand Awareness dan Brand Image terhadap Brand Loyalty: Kasus Pengguna Somethinc di Kota Bandung - Ramadhan, Salsa Putri; Raharso, Sri; Tjahjawati, Sri Surjani (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The rising awareness of self-care and beauty has driven the growth of local beauty companies in Indonesia. The increasingly competitive market presents a challenge for Somethinc as a local beauty company. Loyalty becomes a crucial aspect in facing this competition, which can be formed through brand awareness and brand image. This study aims to examine the influence of brand awareness and brand image on brand loyalty among Somethinc users in Bandung City. The research method used is descriptive quantitative with a sample of 220 respondents selected using non-probability and purposive sampling techniques. Data were collected through a Likert-scale questionnaire. Data analysis includes validity and reliability tests, classical assumption tests (normality, heteroscedasticity, multicollinearity), descriptive statistics, correlation analysis, multiple linear regression, coefficient of determination, as well as t-test and F-test. The results indicate that the data is normal and there is a strong correlation between the variables of brand awareness and brand image with the variable of brand loyalty, with an influence of 52.3%. These findings show that brand awareness and brand image have a positive and significant impact on the brand loyalty of Somethinc users in Bandung City. Keywords: Brand Awareness, Brand Image, Brand Loyalty